2018
DOI: 10.19084/rca17242
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of Brachiaria decumbens in grazing systems

Abstract: Plant Ecophysiology was used as a tool to interpret the responses and adaptation of pastures to environmental conditions. The objective of this study was to evaluate ecophysiological parameters in Brachiaria decumbens grown in different grazing systems in the Cerrado's biome in the south state of Maranhão, Brazil. The experiment was conducted in a completely randomized design with nine replications, using a 3×2×3 factorial arrangement consisted of three grazing management systems (silvopastoral, a rotation sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The grasses inserted in the thinned area, due to their C 4 photosynthetic mechanism, used water and captured solar radiation incident on the top of the canopy more efficiently than plants with the C 3 mechanism; moreover, the presence of the woody stratum in the area allows the quantum efficiency of photosystems to be improved. Ramos et al (2018), when evaluating the grass Brachiaria decumbens in different manipulated areas, observed that when the grass was cultivated in an area containing a woody stratum it had a better quantum efficiency (0.82) of photosystem II (Fv/Fm) than when grown in a deforested area. According to those authors, values lower than 0.75 denote photoinhibitory damage in the PSII reaction centers.…”
Section: Trialmentioning
confidence: 99%
“…The grasses inserted in the thinned area, due to their C 4 photosynthetic mechanism, used water and captured solar radiation incident on the top of the canopy more efficiently than plants with the C 3 mechanism; moreover, the presence of the woody stratum in the area allows the quantum efficiency of photosystems to be improved. Ramos et al (2018), when evaluating the grass Brachiaria decumbens in different manipulated areas, observed that when the grass was cultivated in an area containing a woody stratum it had a better quantum efficiency (0.82) of photosystem II (Fv/Fm) than when grown in a deforested area. According to those authors, values lower than 0.75 denote photoinhibitory damage in the PSII reaction centers.…”
Section: Trialmentioning
confidence: 99%